Vertebrate tracks from the Paso Córdoba fossiliferous site (Anacleto and Allen formations, Upper Cretaceous), Northern Patagonia, Argentina: Preservational, environmental and palaeobiological implications - Díaz Martínez, Ignacio (2018)
The Paso Córdoba fossiliferous site (Río Negro, Northern Patagonia) is one of the first Mesozoic fossiliferous localities studied in Argentina. There, turtle, crocodile and dinosaur remains as well as dinosaur and bird tracks have been recorded. Recently, a new locality with vertebrate tracks, the Cañadón del Desvío, has been discovered in Paso Córdoba. Six track-bearing layers were located in outcrops belonging to the Anacleto (lower to middle Campanian, Neuquén Group) and Allen (middle Campanian-lower Maastrichtian, Malargüe Group) formations. The Cañadón del Desvío locality reveals that vertebrate trace fossils are distributed in two distinct environments, floodplains of a meandering fluvial to shallow lacustrine system and a wet interdune deposit that is associated to an aeolian setting. Also, in the logged section several soft sediment deformation structures were found. In regard of this, a sedimentary facies analysis is provided in order to assess the palaeoenvironmental implications of this new record. The analysed tracks are preserved in cross-sections, on bedding-planes and as natural casts. When it is possible, the tracking surface, true tracks, undertracks and overtracks/natural casts have been identified and the track preservation and the formation history of the tracksite are discussed. Only two tracks preserve enough anatomical details to relate them with their trackmakers, in this case hadrosaurid dinosaurs. The stratigraphical, facial and palaeoenvironmental data of this study support the idea of a transitional passage between the Anacleto and Allen Formation in Paso Córdoba. The presence of hadrosaurid dinosaur tracks suggests that the upper part of the log, where this kind of tracks were found, likely belong to Allen Formation due to this dinosaurs appear in the Southern Hemisphere in this epoch. The sum of osteological and ichnological remains improve the Paso Córdoba palaeofaunistic knowledge. The presence of six different levels in which the trackmakers walked reflects the abundance of vertebrates in the transition between Anacleto and Allen formations.